2004
DOI: 10.1016/j.jsb.2003.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Lipid domain formation and dynamics in giant unilamellar vesicles explored by fluorescence correlation spectroscopy

Abstract: Lipids in eukaryotic cell membranes have been shown to cluster in "rafts" with different lipid/protein compositions and molecular packing. Model membranes such as giant unilamellar vesicles (GUVs) provide a key system to elucidate the physical mechanisms of raft assembly. Despite the large amount of work devoted to the detection and characterization of rafts, one of the most important pieces of information still missing in the picture of the cell membrane is dynamics: how lipids organize and move in rafts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 66 publications
16
125
1
Order By: Relevance
“…The higher ZnO concentration leads to the enhancement of the D reduction. This is in line with other studies, which reported that a noticeable influence over lipid membranes is observed at higher concentrations of cholesterol, proteins or other nanoparticles [26][27][28][29][30][31][32]. This effect is explained by reduction of free area because of tighter lipid packing.…”
Section: Zno and Tio 2 Np's Interaction With Slbsupporting
confidence: 92%
“…The higher ZnO concentration leads to the enhancement of the D reduction. This is in line with other studies, which reported that a noticeable influence over lipid membranes is observed at higher concentrations of cholesterol, proteins or other nanoparticles [26][27][28][29][30][31][32]. This effect is explained by reduction of free area because of tighter lipid packing.…”
Section: Zno and Tio 2 Np's Interaction With Slbsupporting
confidence: 92%
“…Furthermore, neither dye was enriched at the leading edge. A hallmark of liquid-ordered domains is their sensitive dependence on membrane cholesterol (Kahya et al, 2004). In a second approach, we therefore used methyl-␀-cyclo-dextran treatment to extract 35% of plasma membrane cholesterol from keratocytes prior to FLOID.…”
Section: The Barrier Does Not Depend On Lipid Microdomainsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] In this report, we measure the collective mobility of a number of membrane components as a function of temperature in living cell membranes by fluorescence correlation spectroscopy (FCS). [19][20] Since collective mobility exhibits a discontinuity as a system passes through a miscibility phase transition, [21][22] these observations are expected to reveal the phase transition, even in cases where the phase domains are too small to resolve by direct imaging. We support this by a variety of Monte-Carlo and atomistic simulations, which show that FCS measurements of tagged particle diffusion would capture such transitions.…”
Section: Introductionmentioning
confidence: 99%